1996
DOI: 10.1002/(sici)1097-0215(19961021)69:5<420::aid-ijc12>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Human brain tumorO6-methylguanine-DNA methyltransferase mRNA and its significance as an indicator of selective chloroethylnitrosourea chemotherapy

Abstract: , .Akita 010, 'j,,an. 06-methylguanine-DNA methyltransferase (MGMT) removes and repairs chloroethylnitrosourea (CENU)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 6 publications
3
21
0
Order By: Relevance
“…MGMT is one of the most important genes for ACNU resistance. 6,7,10,30 According to our results, the tumor with RQV of MGMT м1 in real-time quantitative RT-PCR should not be treated by ACNU.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…MGMT is one of the most important genes for ACNU resistance. 6,7,10,30 According to our results, the tumor with RQV of MGMT м1 in real-time quantitative RT-PCR should not be treated by ACNU.…”
Section: Discussionmentioning
confidence: 71%
“…5,10 Some authors, including us, have reported that MGMT expression is closely correlated with the clinical or experimental resistance of brain tumors to ACNU. 30,49 There are at least 2 possible approaches to increase the effectiveness of nitrosoureas in the presence of MGMT; i.e., avoid using nitrosoureas in MGMT active tumors as in our approach and overcome the resistance of MGMT to nitrosoureas. MGMT is different from other enzymes because it is consumed.…”
Section: Discussionmentioning
confidence: 99%
“…Although the cytotoxicity of chloroethylating agents and methylating agents can be attributed to quite different DNA lesions, both depend upon initial adduct formation at the O 6 -position of guanine (9,55,56). Several preclinical and clinical studies have strongly suggested that the DNA repair enzyme MGMT, with reverse alkylation at the O 6 -position of guanine, plays an important role in cellular resistance to chlorethylation or methylation damage at the O 6 -position of guanine DNA (10,(13)(14)(15)(16)(17)(18)26,(57)(58)(59)(60)(61)(62). In human cancer, the MGMT gene is not commonly mutated or deleted, and loss of MGMT function is most frequently due to epigenetic changes, particularly promoter hypermethylation (22,28,63), which cause MGMT transcriptional silencing in cells with defective O 6 -methylguanine repair (22,28,64,65).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of trials showed a relationship between low MGMT and better therapeutic response in patients with malignant gliomas on treatment with BCNU 16,17,39,40 or temozolomide. 19,41,42 Some studies, however, failed to show a correlation.…”
Section: Therapeutic Response Of Patientsmentioning
confidence: 99%